2018
DOI: 10.4317/jced.54444
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of 1% Betadine mouthwash on the incidence of dry socket after mandibular third molar surgery

Abstract: BackgroundDry socket or alveolar osteitis is a delayed healing of alveolar bone after exodontia causing moderate to severe pain 2-4 days after extraction of teeth. Antibacterial agents such as antibiotics and chlorhexidine have been previously proved to prevent or reduce the incidence of dry socket. Betadine is a mixture of iodine and povidone which has bactericidal, antifungal and antiviral effects. The aim of the present study was to evaluate the effect of preoperative povidone iodine 1% mouthwash before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
3
10
0
1
Order By: Relevance
“…9 There are several studies by various authors who link poor oral hygiene to the incidence of dry socket. Most patients in the present study with dry socket were found to have "fair" oral health (nonsignificant) and it is in agreement to Hasheminia D et al 4 Various other authors also state that satisfactory oral hygiene is a factor that leads to a decrease in the incidence of dry socket. 10,11 The outcomes of the present study demonstrate that females had a higher incidence of dry socket in comparison to their male counterparts and was statistically significant.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…9 There are several studies by various authors who link poor oral hygiene to the incidence of dry socket. Most patients in the present study with dry socket were found to have "fair" oral health (nonsignificant) and it is in agreement to Hasheminia D et al 4 Various other authors also state that satisfactory oral hygiene is a factor that leads to a decrease in the incidence of dry socket. 10,11 The outcomes of the present study demonstrate that females had a higher incidence of dry socket in comparison to their male counterparts and was statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement to various other researchers and the reason for this could be due to the cause that hormones, combined with oral contraceptive pills that can progress the fibrinolytic actions in blood and women's saliva during their menstrual cycle leading to a higher incidence of dry socket. 4,8,[12][13] The findings of the present study are in agreement to Hasheminia D et al 4 and Mesgarzadeh et al 14 who introduced and stated that povidone iodine 1% mouthwash as a cause of decreased incidence of dry socket. Our results also highlighted a significant relationship between the use of the povidone iodine 1% mouthwash and incidence of dry socket, and was in disagreement to the findings of Sweet et al 15 The diminished occurrence of in occurrence of dry socket after utilization of a topical antimicrobial substance shows light on the role on bacteria in the development of a dry socket.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations